2022
DOI: 10.22541/au.165216062.20582135/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Management of Anxiety in Coronary Artery Bypass Grafting Patients: The influence of Chair Aerobics and Nadisodhana Pranayama A Pilot Randomized Clinical Trial

Abstract: Background Anxiety is a primary concern affecting the prognosis of CABG patients. Relieving anxiety is thus a component of management in patients with CABG. Also, patients with bypass surgery express compromise in exercise tolerance. We use two feasible and cost-effective treatment techniques to know the improvement in symptoms of anxiety and exercise tolerance. Objective To evaluate the efficacy of chair aerobics and pranayama on anxiety in patients who underwent CABG. We hypothesized that there would be an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…25,26 The area of anxiety was unexplored, and also quality research is required in this field to provide evidence. 27 We found that nadisodhana pranayama The p-value is more than 0.05 which shows that gender distributed equally. The mean value showed significant difference in all the parameters.…”
Section: Discussionmentioning
confidence: 71%
“…25,26 The area of anxiety was unexplored, and also quality research is required in this field to provide evidence. 27 We found that nadisodhana pranayama The p-value is more than 0.05 which shows that gender distributed equally. The mean value showed significant difference in all the parameters.…”
Section: Discussionmentioning
confidence: 71%